Operador Deslocamento Condicional: Geração de Estados e Medida da Função de Wigner - SOUZA, Simone Ferreira (2006)
We present a feasible proposal for the construction of the conditional displacement operator using a Kerr medium between two beam splitters fed from coherent states highly excited. The device allows the implementation of the generation of a new class of states the quantized electromagnetic field (arbitrary superpositions of states with states moved) and the measurement of the Wigner function for arbitrary states. The application special case of the number of states and study their nonclassical properties were also considered.